Prefrontal dopamine regulates fear reinstatement through the downregulation of extinction circuits - Natsuko Hitora-Imamura; Yuki Miura; Chie Teshirogi; Yuji Ikegaya; Norio Matsuki; Hiroshi Nomura (eLife, 2015)
Prevention of relapses is a major challenge in treating anxiety disorders. Fear reinstatement can cause relapse in spite of successful fear reduction through extinction-based exposure therapy. By utilising a contextual fear-conditioning task in mice, we found that reinstatement was accompanied by decreased c-Fos expression in the infralimbic cortex (IL) with reduction of synaptic input and enhanced c-Fos expression in the medial subdivision of the central nucleus of the amygdala (CeM). Moreover, we found that IL dopamine plays a key role in reinstatement. A reinstatement-inducing reminder shock induced c-Fos expression in the IL-projecting dopaminergic neurons in the ventral tegmental area, and the blocking of IL D1 signalling prevented reduction of synaptic input, CeM c-Fos expression, and fear reinstatement. These findings demonstrate that a dopamine-dependent inactivation of extinction circuits underlies fear reinstatement and may explain the comorbidity of substance use disorders and anxiety disorders.